Facilitating Development Research: Suggestions for Recruiting and Re-Recruiting Children and Families - Hurwitz, Lisa B.; Schmitt, Kelly L.; Olsen, Megan K. (Frontiers in Psychology, 2017)
Recruiting children and families for research studies can be challenging, and re-recruiting former participants for longitudinal research can be even more difficult, especially when a study was not prospectively designed to encompass continuous data collection. In this article, we explain how researchers can set up initial studies to potentially facilitate later waves of data collection; locate former study participants using newer, often digital, tools; schedule families using recruitment phone/email/mail scripts that highlight the many benefits to continued study participation; and confirm appointments with other digital tools. We draw from prior methodological and longitudinal pieces to provide suggestions to others wishing to re-recruit families for longitudinal studies. In addition, we draw upon our own experience conducting a non-prospective longitudinal study six years after an educational intervention, in which we successfully re-located 122 (90%) and interviewed 101 of 136 (83% of the located sample and 74% of the full original sample) parents and their early adolescent children. Although the majority of participants were recruited via original contact information (especially phone numbers), using a range of strategies to recruit (e.g., search engines focused on contact information, social media) and motivate participation (e.g., multifaceted phone/email/mail scheduling scripts, flexibility in location and means of participation) yielded a more desirable sample size at relatively low costs.